Understanding the societal resistance to the uptake of AI and other emerging technologies in auditing firms: A South African perspective - Van Staden, Jayde (College of Accounting, 2024)
Digital transformation has seen the uptake of emerging technologies at a rapid rate, now more than ever after the COVID-19 pandemic. Audit firms are no exception to this, yet many auditors and audit trainees still show a reluctance towards integrating technology into their work processes. Considering that almost 80% of all Fortune 500 accounting functions will be automated within the next decade, it is imperative to analyse the areas that South African firms can improve in, to gain a seat at the global table, enhance their competitive advantage and leverage technology to improve socioeconomic issues like unemployment that plague the South African economy. Using Qualtrics as a method of enquiry and descriptive analytics to determine the average mean for each category of question, 100 usable questionnaire responses from varying age groups, roles and firm sizes demonstrate that social factors, such as, the lack of support from senior management, as well as limited training and guidance relating to technology integration, are still holding them back. The resource gap between small and large firms seems to be increasing with the onset of emerging technologies altering the audit landscape, as small firms are constrained by financial and nonfinancial constraints such as costs and lack of dedicated IT personnel. Luckily, these constraints are not deterring small firms from seeing the benefits of audit integration, while large firms are pursuing it at a rapid rate.